If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3(x + 2) = 7(2x + 5) Reorder the terms: 4 + -3(2 + x) = 7(2x + 5) 4 + (2 * -3 + x * -3) = 7(2x + 5) 4 + (-6 + -3x) = 7(2x + 5) Combine like terms: 4 + -6 = -2 -2 + -3x = 7(2x + 5) Reorder the terms: -2 + -3x = 7(5 + 2x) -2 + -3x = (5 * 7 + 2x * 7) -2 + -3x = (35 + 14x) Solving -2 + -3x = 35 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -2 + -3x + -14x = 35 + 14x + -14x Combine like terms: -3x + -14x = -17x -2 + -17x = 35 + 14x + -14x Combine like terms: 14x + -14x = 0 -2 + -17x = 35 + 0 -2 + -17x = 35 Add '2' to each side of the equation. -2 + 2 + -17x = 35 + 2 Combine like terms: -2 + 2 = 0 0 + -17x = 35 + 2 -17x = 35 + 2 Combine like terms: 35 + 2 = 37 -17x = 37 Divide each side by '-17'. x = -2.176470588 Simplifying x = -2.176470588
| -145=5(3b-8) | | 3x+4=-5x | | 180=90+3x | | 2t+(3+5t)(4)= | | X^2+3x-195.5= | | 5x+9=2x+13 | | 4-(3x+2)=7(2x+5) | | -4+3x=-6+10 | | -15u-6u-12u-20=13 | | 4x^2+4xy+y^2-100= | | 14.50=p-53 | | X=3y-2400 | | -55-11x=7(9-10x) | | 3x+7y-21=0 | | -(b-3)+7=4 | | 6x+4[7-(x-2)]= | | 2n^2-2n+5=400 | | 5x+1+12x-1=17 | | 5(x-14)=4(x-7) | | 4y+1=56-9 | | 7x-2+3= | | 12=7+3x+1 | | 10-p=-8 | | x^2+10x=-38 | | -3(2x+1)+(3x+2)= | | 1.2+1.5x=5.7 | | 2(d-6)-1=1 | | -2(s-4)-2=2 | | (x+3)(x-2)(x-8)=0 | | n^2+n=22 | | 2y^2-14y+24=0 | | .3x-4x-1=3 |